2017
DOI: 10.1038/celldisc.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

Hemojuvelin regulates the innate immune response to peritoneal bacterial infection in mice

Abstract: Hereditary hemochromatosis and iron imbalance are associated with susceptibility to bacterial infection; however, the underlying mechanisms are poorly understood. Here, we performed in vivo bacterial infection screening using several mouse models of hemochromatosis, including Hfe (Hfe−/−), hemojuvelin (Hjv−/−), and macrophage-specific ferroportin-1 (Fpn1fl/fl;LysM-Cre+) knockout mice. We found that Hjv−/− mice, but not Hfe−/− or Fpn1fl/fl;LysM-Cre+ mice, are highly susceptible to peritoneal infection by both G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
2
8
1
Order By: Relevance
“…In hepatoma‐derived cells, Hjv forms a multi‐protein membrane complex with the hemochromatosis protein and transferrin receptor 2 . Recently, we found that Hjv can interact with interleukin 12 receptor subunit beta 1 . In this study, our results provide the first evidence that Hjv serves as a coreceptor for TβRII in skeletal muscle, conferring an additional layer of regulation to control TGF‐β1 signalling.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In hepatoma‐derived cells, Hjv forms a multi‐protein membrane complex with the hemochromatosis protein and transferrin receptor 2 . Recently, we found that Hjv can interact with interleukin 12 receptor subunit beta 1 . In this study, our results provide the first evidence that Hjv serves as a coreceptor for TβRII in skeletal muscle, conferring an additional layer of regulation to control TGF‐β1 signalling.…”
Section: Discussionmentioning
confidence: 52%
“…45 Recently, we found that Hjv can interact with interleukin 12 receptor subunit beta 1. 46 In this study, our results provide the first evidence that Hjv serves as a coreceptor for TβRII in skeletal muscle, conferring an additional layer of regulation to control TGF-β1 signalling. Further work is needed to determine the precise mechanism by which Hjv inhibits TGF-β1 signalling in skeletal muscle.…”
Section: Discussionmentioning
confidence: 56%
“…The LysM Cre driver is highly efficient in recombining genes in macrophages and monocytes, 4042 and has been shown to cause gene recombination in granulocytes. 4345 Although LysM Cre appears reliable in recombining target genes in cultured microglia, recombination by LysM Cre driver in microglia in vivo not efficient, 2023 reported as less than 10–25%.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, invasion of cells and macrophages with bacteria, such as Listeria , Mycobacteria, or Salmonella , induces alternative mechanisms. Specifically, the upregulation of FPN by different mechanisms results in macrophage iron efflux and limitation of bacterial growth [50,51,52,53,54]. In addition, M1 macrophages and other immune cells produce several factors, such as lipocalin-2, lactoferrin, and calprotectin, which limit the bacterial access to iron [55,56,57].…”
Section: Introductionmentioning
confidence: 99%